'It is a crime to be abusive towards the president': A case study on media freedom and journalists' autonomy in museveni's uganda. Issue 3 (2nd July 2016) - Meyen, Michael; Fiedler, Anke; Schamberger, Kerem
ABSTRACT: Using the case of the hybrid media system of Uganda and Schimank's approach of agent-structure dynamics, this article argues that media freedom and journalists' autonomy first and foremost depend on society's expectations of the media system. Closely linked to those informal structures of expectations which are path and time dependent, journalists' room for manoeuvre is limited by the resources allocated to individual and collective media actors. In a first step and following Schimank's approach, the article presents a category system that could drive the analysis of media freedom in Uganda and beyond. The empirical study is based on research material consisting of 30 expert interviews, two elite round tables on site in Uganda and documents. This material shows that both journalists' working conditions and (related to this and even more important) their perception among the ruling elites, public administrations and those governed, limit media freedom. It is precisely the media's relative societal position which allowed the government to implement a system of media laws and media regulation authorities which creates arbitrariness and, therefore, a feeling of insecurity within the profession.